Electrolyte, battery and electric device
Patent Information
- Application Number
- CN202611318678.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-27
- Publication Date
- 2026-10-30
AI Technical Summary
导致界面膜结构无序、阻抗升高、氧化还原可逆性下降,不仅无法协同提升电池性能,反而加剧副反应发生;同时,高压循环过程中,电解液易发生氧化分解,电池内部产生的大量自由基会持续破坏电极界面结构,引发电解液持续耗损、活性锂损失及容量衰减
[0032]本申请提供的电解液,针对现有的电解液添加剂体系难以满足高电压适配性、阻燃安全性、长循环寿命和热稳定性的问题,以吩噻嗪基团为母核协同取代或未取代的哌嗪基团的烷基链以及取代或未取代的磺酰胺基团的有机物作为添加剂,这一添加剂在电解液体系中,各个基团之间互相配合,协同作用,具有自由基清除阻燃、高压抗氧化、有序界面成膜、可逆氧化还原容量补偿的多功能集成效果,突破了现有添加剂功能单一、复配拮抗、金属离子副反应的技术瓶颈。
Smart Images

Figure SMS_10 
Figure SMS_11 
Figure SMS_12
Abstract
Description
Technical Field
[0001] This application belongs to the field of battery technology and relates to an electrolyte, a battery, and an electrical device. Background Technology
[0002] With the large-scale application of lithium-ion batteries in new energy vehicles, high-end energy storage, aerospace and other fields, the market has put forward higher requirements for the batteries' high voltage adaptability, flame retardant safety, long cycle life and thermal stability.
[0003] In addition to water-based solvents and lithium salts, existing electrolytes often include electrolyte additives for modification. However, current commercial electrolyte additives generally suffer from limited functionality, only achieving single-function modifications such as film formation, oxidation resistance, and flame retardancy, failing to meet multiple performance requirements including electrochemical stability, thermal safety, interface regulation, and capacity retention.
[0004] In practical applications, to compensate for the performance deficiencies of single additives, the industry often uses a combination of multiple functional additives. However, antagonistic effects can easily occur between the compounded components. For example, some flame retardants can inhibit the preferential reduction of film-forming additives at the negative electrode, leading to a decrease in film quality. Secondly, the introduction of multiple additives increases the complexity of the electrolyte system, raising manufacturing costs and making quality control more difficult. Furthermore, complex additive systems often struggle to form a stable interface layer between high-voltage positive electrodes and sensitive negative electrodes (such as silicon negative electrodes). For instance, while some sulfur- or phosphorus-containing additives can remove HF or provide flame retardancy, their decomposition products may catalyze lithium salt decomposition or induce metal ion dissolution, further exacerbating side reactions. This results in disordered interface film structure, increased impedance, and decreased redox reversibility, failing to synergistically improve battery performance and instead exacerbating side reactions. Simultaneously, during high-voltage cycling, the electrolyte is prone to oxidative decomposition, and the large number of free radicals generated inside the battery continuously damages the electrode interface structure, leading to continuous electrolyte consumption, loss of active lithium, and capacity decay. In addition, residual or side-reaction-generated transition metal ions in the battery system are prone to migration, dissolution and deposition, inducing side reactions, damaging the stability of the solid electrolyte interphase (SEI) film, further aggravating cycle decay and increasing internal resistance, and seriously restricting the battery cycle life and safety performance.
[0005] Therefore, there is an urgent need for a multifunctional integrated electrolyte that can achieve free radical scavenging and flame retardancy, high-voltage oxidation resistance, ordered interfacial film formation, and reversible redox capacity compensation without the antagonistic effect of additives. Summary of the Invention
[0006] To address the shortcomings of existing technologies, the purpose of this application is to provide an electrolyte, a battery, and an electrical device. The electrolyte provided in this application uses alkyl chains of phenthiazide groups with substituted or unsubstituted piperazine groups as the parent core, and organic compounds with substituted or unsubstituted sulfonamide groups as additives. This provides a multi-functional integrated effect, including free radical scavenging and flame retardancy, high-voltage oxidation resistance, ordered interfacial film formation, and reversible redox capacity compensation. It overcomes the technical bottlenecks of existing additives, such as single function, compound antagonism, and metal ion side reactions, thereby improving the battery's high-voltage stability, flame retardant safety, cycle life, and energy density.
[0007] To achieve the purpose of this application, the following technical solution is adopted:
[0008] In a first aspect, this application provides an electrolyte comprising a non-aqueous solvent, a lithium salt, and a first additive; the first additive having R1-(CH2) n The structural formula described in Ar-R2:
[0009] Wherein, R1 is selected from substituted or unsubstituted piperazine groups, Ar is a phenothiazine group, R2 is selected from substituted or unsubstituted sulfonamide groups, and n is any integer between 1 and 6.
[0010] In one embodiment of this application, in the first additive, R1 is selected from an N-substituted piperazine group, and the substituent group in the piperazine group is selected from substituted or unsubstituted straight-chain or branched C1-C4 alkyl groups.
[0011] In one embodiment of this application, -(CH2) is attached to the N-position of the phenothiazine group. n -R1.
[0012] In one embodiment of this application, the C at the 2-position of the phenothiazine group is linked to -R2.
[0013] In one embodiment of this application, in the first additive, R2 is selected from a substituted sulfonamide group, and the substituted group in the sulfonamide group is selected from substituted or unsubstituted straight-chain or branched C1-C4 alkyl groups.
[0014] In one embodiment of this application, n in the first additive is any integer between 3 and 6.
[0015] In one embodiment of this application, the electrolyte has at least one of the following structural formulas (1) to (6):
[0016] .
[0017] In one embodiment of this application, based on the total mass of the non-aqueous solvent, the lithium salt, and the first additive being 100wt%, the mass percentage of the first additive is 0.05wt% to 5wt%, preferably 0.2wt% to 2wt%.
[0018] In one embodiment of this application, the non-aqueous solvent includes carbonate organic solvents and / or ether solvents.
[0019] In one embodiment of this application, based on a total mass of 100wt% for the non-aqueous solvent, the lithium salt, and the first additive, the mass percentage of the non-aqueous solvent is 80wt% to 90wt%.
[0020] In one embodiment of this application, the lithium salt includes a fluorine-containing lithium salt.
[0021] In one embodiment of this application, the concentration of the lithium salt is 0.8 mol / L to 1.5 mol / L.
[0022] In one embodiment of this application, the electrolyte further includes a second additive, which is selected from film-forming additives, including at least one of fluoroethylene carbonate, vinylene carbonate, or 1,3-propanesulfonate lactone.
[0023] In one embodiment of this application, the total mass of the non-aqueous solvent, the lithium salt, and the first additive is 100 wt%, and the mass of the second additive added is 0.1 wt% to 8 wt%.
[0024] In one embodiment of this application, the electrolyte further includes a third additive, which is selected from heat-stabilizing additives, including at least one of lithium difluorophosphate, trimethyl phosphate, or triphenyl phosphite.
[0025] In one embodiment of this application, the total mass of the non-aqueous solvent, the lithium salt, and the first additive is 100 wt%, and the mass of the third additive added is 0.1 wt% to 5 wt%.
[0026] In one embodiment of this application, the electrolyte further includes a fourth additive, which is selected from high-voltage antioxidant additives, including at least one of adiponitrile and / or vinyl sulfate.
[0027] In one embodiment of this application, based on a total mass of 100 wt% for the non-aqueous solvent, the lithium salt, and the first additive, the mass of the fourth additive added is 0.1 wt% to 2 wt%.
[0028] In a second aspect, this application provides a battery comprising the electrolyte as described in the first aspect.
[0029] In one embodiment of this application, the operating voltage of the battery is ≥4.4V.
[0030] Thirdly, this application also provides an electrical device comprising a battery as described in the second aspect.
[0031] Compared with the prior art, this application has the following advantages:
[0032] The electrolyte provided in this application addresses the problem that existing electrolyte additive systems cannot meet the requirements of high voltage compatibility, flame retardant safety, long cycle life, and thermal stability. It uses alkyl chains of substituted or unsubstituted piperazine groups and organic compounds of substituted or unsubstituted sulfonamide groups as additives, with phenothiazine groups as the parent core. In the electrolyte system, the various groups cooperate and work synergistically, resulting in a multi-functional integrated effect of free radical scavenging and flame retardancy, high-voltage oxidation resistance, ordered interfacial film formation, and reversible redox capacity compensation. This breaks through the technical bottlenecks of existing additives, such as single function, compound antagonism, and metal ion side reactions. Detailed Implementation
[0033] The technical solution of this application will be further described below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely to help understand this application and should not be regarded as specific limitations on this application.
[0034] In this application, technical features or solutions described using open-ended terms such as "comprising" or "including" do not exclude additional non-conflicting elements beyond those listed unless otherwise specified. They are considered to disclose both closed-ended features or solutions consisting solely of the listed elements and open-ended features or solutions that may include additional non-conflicting elements beyond those listed. For example, if A includes a1, a2, and a3, unless otherwise specified, this means that A may consist only of a1, a2, and a3, or it may include other non-conflicting elements in addition to a1, a2, and a3. This corresponds to the disclosure of technical solutions where "A consists of a1, a2, and a3" and "A includes not only a1, a2, and a3, but also other non-conflicting elements."
[0035] The above description is only a specific embodiment of this application, but the protection scope of this application is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in this application fall within the protection and disclosure scope of this application.
[0036] In one embodiment, this application provides an electrolyte comprising a non-aqueous solvent, a lithium salt, and a first additive; the first additive having R1-(CH2). nThe structural formula described in Ar-R2:
[0037] Wherein, R1 is selected from substituted or unsubstituted piperazine groups, Ar is a phenothiazine group, R2 is selected from substituted or unsubstituted sulfonamide groups, and n is any integer between 1 and 6, for example, n can be 1, 2, 3, 4, 5 or 6, etc.
[0038] The electrolyte provided in this application addresses the problem that existing electrolyte additive systems cannot meet the requirements of high voltage compatibility, flame retardant safety, long cycle life, and thermal stability. It uses alkyl chains of substituted or unsubstituted piperazine groups and organic compounds of substituted or unsubstituted sulfonamide groups as additives, with phenothiazine groups as the parent core. In the electrolyte system, the various groups cooperate and work synergistically, resulting in a multi-functional integrated effect of free radical scavenging and flame retardancy, high-voltage oxidation resistance, ordered interfacial film formation, and reversible redox capacity compensation. This breaks through the technical bottlenecks of existing additives, such as single function, compound antagonism, and metal ion side reactions.
[0039] Among them, the sulfur and nitrogen atoms on the phenothiazine group core of the first additive have high electrochemical activity and can preferentially undergo electrochemical reactions on the positive and negative electrode surfaces to participate in the formation of a stable sulfur / nitrogen-containing SEI / CEI film, which isolates the electrolyte from direct contact with the electrode and inhibits the dissolution of transition metals and solvent decomposition. At the same time, the tricyclic aromatic conjugated structure in this group can efficiently capture active free radicals generated by electrolyte decomposition under high temperature / high voltage through electron delocalization effect, terminate the chain reaction, inhibit electrolyte oxidation decomposition and thermal runaway from the root, and significantly improve the flame retardancy of the electrolyte. In addition, this core group has reversible redox properties and can gain or lose electrons during charging and discharging, which has the capacity compensation effect of redox medium, makes up for the first irreversible capacity loss, improves the battery energy density, and has no risk of metal ion side reactions.
[0040] In the first additive, the dinitrogen atom heterocyclic structure in the piperazine group can interact with Li. + The formation of weak coordination bonds reconstructs the lithium-ion solvation sheath, reduces the lithium-ion desolvation energy, and improves ion transport rate and rate performance; the tertiary amine nitrogen atom on the piperazine ring can be directionally adsorbed on the negative electrode surface, synergistically with the parent nucleus group, guiding the orderly growth of the SEI film and forming a dense, low-resistance interfacial film; the basic nitrogen atom can neutralize trace amounts of HF in the electrolyte, inhibit interfacial corrosion, and improve cycle stability; and the phenothiazine group and the substituted or unsubstituted piperazine group in the first additive are connected by an alkyl chain, this -(CH2) nThe flexible alkyl chain can improve the compatibility of additives with non-aqueous solvents, prevent additive precipitation at high concentrations, and enhance the storage stability of electrolytes. Furthermore, this characteristic linkage also regulates the steric hindrance and electrochemical potential of the phenothiazine core, optimizes the redox reversibility and film-forming potential of the additive, and avoids the occurrence of preferential side reactions.
[0041] In the first additive, the substituted or unsubstituted sulfonamide group has strong polarity, which can significantly improve the dielectric constant of the electrolyte, promote the dissociation of lithium salt, especially fluorinated lithium salt, and improve the ionic conductivity of the electrolyte. At the same time, the sulfonyl group can cooperate to participate in the interfacial film formation of the positive and negative electrodes, forming a stable interfacial layer containing sulfur-oxygen bonds, and enhancing the high temperature resistance and oxidation resistance of the SEI / CEI film. This group also has excellent hydrogen bonding compatibility with non-aqueous solvents, further improving the dispersion uniformity of the additive in the electrolyte.
[0042] The electrolyte provided in this application achieves multi-functional integration of free radical scavenging and flame retardancy, high-voltage anti-oxidation, ordered interface film formation, and reversible redox capacity compensation through the precise design of single-molecule multi-group additives. This breaks through the technical bottlenecks of existing additives with single function, compound antagonism, and metal ion side reactions, and simultaneously improves the high-voltage stability, flame retardant safety, cycle life and energy density of the battery.
[0043] In some embodiments, in the first additive, R1 is selected from an N-substituted piperazine group, and the substituent group in the piperazine group is selected from substituted or unsubstituted straight-chain or branched C1-C4 alkyl groups, such as C1 alkyl, C2 alkyl, C3 alkyl or C4 alkyl.
[0044] This application involves alkyl substitution at the N-position of the piperazine group, especially substitution with low molecular weight (C1-C4 alkyl), which can control the spatial configuration of the molecule without affecting its reactivity with Li. + While forming weak coordination bonds, it can simultaneously maintain reversible redox activity (capacity compensation) and low interfacial impedance (film formation), and its moderate electron-donating ability can effectively stabilize free radical adducts.
[0045] In some embodiments, -(CH2) is attached to the N-position of the phenothiazine group. n -R1.
[0046] In some embodiments, the C at the 2-position of the phenothiazine group is linked to -R2.
[0047] In some embodiments, in the first additive, R2 is selected from substituted sulfonamide groups, wherein the substituted group in the sulfonamide group is selected from substituted or unsubstituted straight-chain or branched C1-C4 alkyl groups.
[0048] In this application, C1-C4 alkyl substitution, especially dimethyl substitution, is performed in the sulfonamide group to eliminate the -NH bond, avoid proton side reactions, and ensure greater stability in high-voltage battery systems.
[0049] In some embodiments, n in the first additive is any integer between 3 and 6, such as 3, 4, 5 or 6.
[0050] The -(CH2) provided in this application n In the alkyl chain, further controlling n to any integer between 3 and 6 can more stably balance the solvent compatibility, electrochemical potential, and film-forming activity of the additive, resulting in more suitable steric hindrance. Furthermore, it allows for precise control of the redox potential of the parent nucleus, achieving a synergistic effect of reversible capacity compensation and ordered film formation. This avoids excessively small steric hindrance, which leads to low film-forming potential and side reactions between the electrolyte and the positive and negative electrodes during storage, affecting the normal use of the electrolyte. It also prevents excessive steric hindrance from reducing the reactivity of the groups, increasing electrolyte viscosity, and affecting performance.
[0051] In some embodiments, the electrolyte has at least one of the following structural formulas (1) to (6):
[0052] .
[0053] It is understandable that, in addition to the structural formulas (1) to (6) above, there are other structural formulas with various combinations. Those skilled in the art can make adaptive selections and adjustments based on specific solutions.
[0054] It is understood that the first additive provided in this application can be purchased directly through commercial means; or it can be synthesized by itself using conventional synthesis methods according to the specific concept. This application does not limit the specific source of the first additive. Under the premise of not violating the overall technical concept of this application, reasonable sources are applicable.
[0055] For example, (1) in the above structural formula is thiopropirazine (CAS No.: 316-81-4).
[0056] In some embodiments, based on the total mass of the non-aqueous solvent, the lithium salt, and the first additive being 100 wt%, the mass percentage of the first additive is 0.05 wt% to 5 wt%, for example, 0.05 wt%, 0.1 wt%, 0.2 wt%, 0.5 wt%, 1 wt%, 1.5 wt%, 2 wt%, 2.5 wt%, 3 wt%, 3.5 wt%, 4 wt%, 4.5 wt%, or 5 wt%.
[0057] Furthermore, based on the total mass of the non-aqueous solvent, the lithium salt, and the first additive being 100wt%, the mass percentage of the first additive is preferably 0.2wt% to 2wt%, for example, 0.2wt%, 0.5wt%, 0.8wt%, 1wt%, 1.2wt%, 1.5wt%, 1.8wt%, or 2wt%.
[0058] In the electrolyte provided in this application, the first additive is selected with a suitable mass ratio of 0.05wt% to 5wt%, which can give full play to its advantages and avoid negative effects. Further adjusting the mass ratio of the first additive to 0.2wt% to 2wt% is more conducive to the formation of a stable interfacial film at the positive / negative electrode interface, and optimizes the redox reversibility and film formation potential of the additive. This can avoid the increase in interfacial impedance, increase in electrolyte viscosity, or influence of redox reversibility potential caused by the addition of excessive additive. Thus, while improving high voltage stability, flame retardant safety, cycle life and thermal stability, it also takes into account the rate performance and energy density of the battery.
[0059] In some embodiments, the non-aqueous solvent includes carbonate organic solvents and / or ether solvents.
[0060] When using non-aqueous solvents, this application combines carbonate organic solvents and ether solvents to balance lithium salt dissociation, ion transport, and additive compatibility, thereby achieving better integration with lithium salts and additives.
[0061] In one embodiment, the carbonate organic solvent includes cyclic carbonates and chain carbonates, which respectively have the advantages of high dielectric constant and low viscosity.
[0062] For example, but not limitingly, the cyclic carbonates include ethylene carbonate (EC) and / or propylene carbonate (PC).
[0063] For example, but not in a limiting sense, the chain carbonate includes at least one of dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), or diethyl carbonate (DEC).
[0064] In one embodiment, the carbonate organic solvent accounts for 70wt% to 90wt% of the non-aqueous solvent by mass, for example, 70wt%, 71wt%, 72wt%, 73wt%, 74wt%, 75wt%, 76wt%, 77wt%, 78wt%, 79wt%, 80wt%, 81wt%, 82wt%, 83wt%, 84wt%, 85wt%, 86wt%, 87wt%, 88wt%, 89wt%, or 90wt%, etc.; the mass ratio of the cyclic carbonate to the chain carbonate is (20~40):(60~80), for example, 20:80, 25:75, 30:70, 35:65, or 40:60, etc.
[0065] For example, but not in a limiting sense, the ether solvent includes at least one of 1,3-dioxolane (DOL), ethylene glycol dimethyl ether (DME), or tetrahydrofuran (THF), preferably a combination of DOL and DME, which can further improve the compatibility of the additive and its low-temperature ion conduction performance.
[0066] In some embodiments, based on the total mass of the non-aqueous solvent, the lithium salt, and the first additive being 100wt%, the mass percentage of the non-aqueous solvent is 80wt% to 90wt%, for example, 80wt%, 81wt%, 82wt%, 83wt%, 84wt%, 85wt%, 86wt%, 87wt%, 88wt%, 89wt%, or 90wt%.
[0067] In some embodiments, the lithium salt includes a fluorinated lithium salt, which includes a primary fluorinated lithium salt and may also include an auxiliary fluorinated lithium salt.
[0068] For example, but not limitingly, the primary fluorinated lithium salt includes lithium hexafluorophosphate (LiPF6) and / or lithium bisfluorosulfonylimide (LiFSI); the secondary fluorinated lithium salt includes lithium difluorooxalate borate (LiDFOB) and / or lithium tetrafluoroborate (LiBF4).
[0069] In some embodiments, the concentration of the lithium salt is 0.8 mol / L to 1.5 mol / L, such as 0.8 mol / L, 0.9 mol / L, 1.0 mol / L, 1.1 mol / L, 1.2 mol / L, 1.3 mol / L, 1.4 mol / L, or 1.5 mol / L.
[0070] In some embodiments, the electrolyte further includes a second additive selected from film-forming additives, including at least one of fluoroethylene carbonate (FEC), vinylene carbonate (VC), or 1,3-propanesulfonate lactone (PS).
[0071] In some embodiments, based on a total mass of 100 wt% of the non-aqueous solvent, the lithium salt, and the first additive, the mass of the second additive is 0.1 wt% to 8 wt%, for example, 0.1 wt%, 0.2 wt%, 0.5 wt%, 1 wt%, 1.5 wt%, 2 wt%, 2.5 wt%, 3 wt%, 3.5 wt%, 4 wt%, 4.5 wt%, 5 wt%, 5.5 wt%, 6 wt%, 6.5 wt%, 7 wt%, 7.5 wt%, or 8 wt%.
[0072] This application involves adding a second additive, different from the first additive, to the electrolyte. This second additive works synergistically with the first additive. The piperazine groups in the first additive are directionally adsorbed on the negative electrode surface, guiding the orderly growth of the SEI film and providing uniform nucleation sites for the reduction and decomposition of the second additive. This avoids the loose and uneven SEI film caused by the local decomposition of the second additive. The highly stable LiF inorganic phase generated by the decomposition of the second additive forms a composite SEI film of "inorganic reinforcing phase + organic flexible matrix" with the sulfur / nitrogen-containing organic components generated by the decomposition of the first additive. This solves the problems of high film brittleness and inability to adapt to the volume expansion of silicon-based negative electrodes caused by single film-forming additives, and also makes up for the defects of insufficient inorganic phase and poor high-temperature resistance of single additive films. Preferably, the mass of the second additive added is 0.1wt%~8wt%, which can exert the synergistic effect of the two and avoid the antagonistic effect of adding multiple additives.
[0073] In some embodiments, the electrolyte further includes a third additive selected from heat-stabilizing additives, including at least one of lithium difluorophosphate (LiPO2F2), trimethyl phosphate (TMP), or triphenyl phosphite (TPPi).
[0074] In some embodiments, the third additive is added at a mass of 0.1wt% to 5wt%, based on a total mass of 100wt% of the non-aqueous solvent, the lithium salt, and the first additive, for example, 0.1wt%, 0.2wt%, 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, or 5wt%.
[0075] This application, based on the first additive, can also add a third additive, different from the first additive, to work together. The first additive terminates the combustion chain reaction through free radical capture, while the third additive captures combustion free radicals in the gas phase and forms a carbonized protective layer in the condensed phase. Together, they form a dual flame-retardant system of "gas phase + condensed phase," improving flame-retardant efficiency. The heat-stabilizing additive removes HF generated from the hydrolysis of lithium salts in the electrolyte, while the first additive inhibits HF formation, forming a dual acid removal system of "prevention + removal," inhibiting high-temperature interface corrosion and significantly improving high-temperature storage and cycling performance. In particular, the combination of lithium difluorophosphate (LiPO2F2) and triphenyl phosphite (TPPi) not only provides dual flame retardancy, but lithium difluorophosphate can also participate in interfacial film formation, generating low-resistance phosphorus-containing components, reducing the interfacial impedance of the film formed by the first additive. Furthermore, the first additive guides the orderly growth of the SEI film, providing uniform sites for the decomposition of LiPO2F2 and avoiding impedance unevenness caused by localized decomposition. By controlling the addition mass of the heat-stabilizing additive to 0.1wt%~5wt%, the synergistic effect of both additives is further enhanced by leveraging their respective advantages.
[0076] In some embodiments, this application does not limit the mass ratio of lithium difluorophosphate (LiPO2F2) and triphenyl phosphite (TPPi) in the heat-stabilizing additive; those skilled in the art can combine them in any proportion according to specific needs.
[0077] In some embodiments, the electrolyte further includes a fourth additive selected from high-voltage antioxidants, including at least one of adiponitrile (ADN) and / or vinyl sulfate (DTD); preferably ADN and DTD.
[0078] In some implementations, this application does not limit the mass ratio of ADN and DTD; those skilled in the art can combine them in any ratio according to specific needs.
[0079] In some embodiments, the fourth additive is added at a mass of 0.1wt% to 2wt%, for example, 0.1wt%, 0.2wt%, 0.5wt%, 0.8wt%, 1wt%, 1.2wt%, 1.5wt%, 1.8wt%, or 2wt%, based on a total mass of 100wt% of the non-aqueous solvent, the lithium salt, and the first additive.
[0080] In addition to the first additive, this application also includes a fourth additive, different from the first additive, in the electrolyte to provide auxiliary promotion. The phenothiazine core of the first additive continuously scavenge free radicals generated by electrolyte decomposition under high voltage, terminating the chain reaction. The high-voltage antioxidant additive can coordinate with the positive electrode transition metal ions, anchoring them on the positive electrode surface and blocking catalytic active sites. The high-voltage antioxidant additive preferentially oxidizes and forms a film on the positive electrode surface, creating a dense and stable CEI film, synergistically forming a triple high-voltage protection system of "free radical scavenging + site anchoring + physical isolation". Furthermore, the first additive inhibits the dissolution of transition metals under high voltage, while the fourth additive enhances the density of the CEI film, preventing the dissolved transition metals from migrating to the negative electrode and damaging the SEI film.
[0081] In one embodiment, this application does not specifically limit the preparation method of the electrolyte in the above embodiments. Without violating the overall technical concept of this application, conventional electrolyte preparation methods are applicable.
[0082] For example, but not in a limiting sense, this application provides a method for preparing the electrolyte described in the above embodiments, the preparation method comprising:
[0083] In a protective atmosphere with a water oxygen content of <1ppm, an organic solvent is mixed, and then a lithium salt is added to obtain a basic electrolyte. Then, a first additive and optional film-forming additives and / or optional heat-stabilizing additives and / or optional high-voltage antioxidant additives are added to the basic electrolyte in a preset ratio. After dissolution and mixing, the electrolyte is obtained.
[0084] Optionally, the protective atmosphere includes a nitrogen atmosphere, an argon atmosphere, or a helium atmosphere, etc.
[0085] In one embodiment, this application provides a battery comprising the electrolyte as described in the above embodiments.
[0086] It is understood that, apart from the electrolyte specified above, the lithium-ion battery in this application has conventional technical solutions in terms of structure, raw materials and preparation process. Those skilled in the art can make adaptive selections and adjustments according to actual needs.
[0087] In some embodiments, the lithium-ion battery includes a positive electrode, a negative electrode, a separator, and an electrolyte.
[0088] This application does not impose any particular limitation on the positive electrode, as long as it achieves the purpose of this application. In some embodiments, the positive electrode sheet includes a positive current collector and a positive active material layer. The positive active material layer is disposed on one or both surfaces of the positive current collector. The aforementioned "surface" can be a portion of the surface of the positive current collector or the entire surface of the positive current collector. This application does not impose any particular limitation on the positive current collector, as long as it achieves the purpose of this application. For example, the positive current collector can contain aluminum foil or aluminum alloy foil, etc. The positive active material layer of this application contains a positive active material. This application does not impose any particular limitation on the type of positive active material, as long as it achieves the purpose of this application. For example, the positive active material can contain at least one of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium-rich manganese-based materials, lithium cobalt oxide, lithium manganese oxide, lithium manganese iron phosphate, or lithium titanate, etc. In this application, the positive active material can also contain non-metallic elements, which can include at least one of fluorine, phosphorus, boron, chlorine, silicon, or sulfur. These elements can further improve the stability of the positive active material. In this application, there are no particular limitations on the thickness of the positive electrode current collector and the positive electrode active material layer, as long as the purpose of this application can be achieved. For example, the thickness of the positive electrode current collector is 5 μm to 20 μm. The thickness of the single-layer positive electrode active material layer is 30 μm to 120 μm. Optionally, the positive electrode active material layer may also include at least one of a conductive agent or a binder. This application does not particularly limit the types of conductive agents and binders in the positive electrode active material layer, as long as the purpose of this application can be achieved. This application does not particularly limit the mass ratio of the positive electrode active material, conductive agent, and binder in the positive electrode active material layer; those skilled in the art can choose according to actual needs, as long as the purpose of this application can be achieved.
[0089] In some embodiments, the positive electrode active material accounts for 85wt% to 98wt% of the mass of the positive electrode active material layer, for example, 80wt%, 81wt%, 82wt%, 83wt%, 84wt%, 85wt%, 86wt%, 87wt%, 88wt%, 89wt%, 90wt%, 91wt%, 92wt%, 93wt%, 94wt%, 95wt%, 96wt%, 97wt%, or 98wt%.
[0090] The separator of this application is disposed between the positive electrode and the negative electrode to separate them. This application does not impose any particular limitation on the separator, as long as it achieves the purpose of this application. For example, the separator material may include, but is not limited to, at least one of polyethylene (PE), polyolefins (PO) primarily composed of polypropylene (PP), polyester (e.g., polyethylene terephthalate (PET) film), cellulose, polyimide (PI), polyamide (PA), spandex, or aramid. The separator type may include at least one of woven membrane, nonwoven membrane, microporous membrane, composite membrane, rolled membrane, or spun membrane. This application does not impose any particular limitation on the separator thickness, as long as it achieves the purpose of this application.
[0091] This application does not impose any particular limitation on the negative electrode, as long as the purpose of this application can be achieved. In some embodiments, the negative electrode includes a negative electrode current collector and a negative electrode active material layer, the negative electrode active material layer being disposed on one or both surfaces of the negative electrode current collector. The aforementioned "surface" can be a portion of the surface of the negative electrode current collector or the entire surface of the negative electrode current collector. For example, the negative electrode current collector may contain copper foil or copper alloy foil, etc. The negative electrode active material layer of this application contains a negative electrode active material. The negative electrode active material includes at least one of artificial graphite, natural graphite, soft carbon, hard carbon, mesophase microcarbon spheres, silicon-based materials, and tin-based materials. Optionally, the negative electrode active material layer may also include at least one of conductive agent or binder. This application does not impose any particular limitation on the types of conductive agent and binder in the negative electrode active material layer, as long as the purpose of this application can be achieved. This application does not impose any particular limitation on the mass ratio of negative electrode active material, conductive agent, and binder in the negative electrode active material layer; those skilled in the art can choose according to actual needs, as long as the purpose of this application can be achieved.
[0092] In some embodiments, the negative electrode active material accounts for 80wt% to 98wt% of the mass of the negative electrode active material layer, for example, 80wt%, 81wt%, 82wt%, 83wt%, 84wt%, 85wt%, 86wt%, 87wt%, 88wt%, 89wt%, 90wt%, 91wt%, 92wt%, 93wt%, 94wt%, 95wt%, 96wt%, 97wt%, or 98wt%.
[0093] In some embodiments, the negative electrode active material includes at least a silicon-based material; the electrolyte provided in this application better solves the problem that single film-forming additives are brittle and cannot adapt to the volume expansion of silicon-based materials; this application does not have any particular restrictions on the specific substances of silicon-based materials, and those skilled in the art can choose according to actual needs, as long as the purpose of this application can be achieved.
[0094] In some embodiments, the silicon-based material includes at least one of silicon-carbon materials, silicon-oxygen materials, nano-silicon materials, porous silicon materials, or silicon alloy materials; the silicon content in the silicon-based material is ≥5 wt%.
[0095] As an example, the silicon-carbon material includes a composite material formed by embedding nano-silicon particles in a carbon matrix, wherein the carbon matrix includes, but is not limited to, at least one of porous carbon, graphite, hard carbon, soft carbon, or mesophase carbon microspheres; the silicon mass percentage in the silicon-carbon material is 5wt% to 50wt%, for example, 5wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, 45wt%, or 50wt%.
[0096] As an example, the general chemical formula of the silicon-oxygen material is SiOx, where 0 < x < 2, such as 0.3, 0.5, 1, 1.5 or 1.8, etc.; the mass percentage of silicon in the silicon-oxygen material is 30wt% to 70wt%, such as 30wt%, 35wt%, 40wt%, 45wt%, 50wt%, 55wt%, 60wt%, 65wt% or 70wt%, etc.
[0097] As an example, the particle size range of the nano-silicon material is 10nm to 500nm, such as 10nm, 50nm, 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm or 500nm, etc.
[0098] As an example, the silicon alloy material includes an alloy material formed of silicon and metal M, wherein the metal M includes, but is not limited to, at least one of Fe, Al, Sn, Mg or Ti; the mass percentage of silicon in the silicon alloy material is 20wt% to 80wt%, for example, 30wt%, 35wt%, 40wt%, 45wt%, 50wt%, 55wt%, 60wt%, 65wt%, 70wt%, 75wt% or 80wt%, etc.
[0099] In some embodiments, the negative electrode active material includes a silicon-based material, and the silicon-based material accounts for 80wt% to 95wt% of the mass of the negative electrode active material layer, for example, 80wt%, 81wt%, 82wt%, 83wt%, 84wt%, 85wt%, 86wt%, 87wt%, 88wt%, 89wt%, 90wt%, 91wt%, 92wt%, 93wt%, or 94wt%, 95wt%, etc.
[0100] Furthermore, whether it is the conductive agent and binder of the positive electrode or the conductive agent and binder of the negative electrode, the conductive agent includes, but is not limited to, conductive carbon black and carbon nanotubes; the binder includes at least one of polytetrafluoroethylene, sodium carboxymethyl cellulose, styrene-butadiene rubber, polyvinylidene fluoride, nitrile rubber, styrene-ethylene-butene-styrene copolymer, styrene-butadiene-styrene copolymer, lithium polyacrylate, sodium polyacrylate, sodium alginate or lithium alginate; the conductive agent includes at least one of acetylene black, Ketjen black, Super-P, carbon nanotubes, carbon fibers or graphene.
[0101] In some embodiments, in addition to the positive electrode, separator, electrolyte, and negative electrode described above, the lithium-ion battery also includes a casing. The casing houses the positive electrode, negative electrode, separator, electrolyte, and other components known in batteries, which are not limited in this application. This application does not impose any particular limitation on the casing; it can be any casing known in the art, as long as it achieves the purpose of this application.
[0102] In some embodiments, the battery operates at a voltage ≥4.4V, such as 4.4V, 4.45V, 4.5V, 4.55V, 4.6V, 4.65V, or 4.7V.
[0103] It should be noted that the battery operating voltage ≥4.4V in this application refers to the battery charging cut-off voltage not being lower than 4.4V.
[0104] The electrolyte provided in this application is suitable for high-voltage battery systems and solves the problems of severe electrolyte oxidation and decomposition and intensified free radical chain reactions under high-voltage conditions.
[0105] In some embodiments, this application provides an electrical device that includes a battery as described in the above embodiments.
[0106] The numerical range described in this application includes not only the point values listed above, but also any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of brevity, this application will not exhaustively list the specific point values included in the range.
[0107] Example 1
[0108] This embodiment provides an electrolyte comprising a non-aqueous solvent, a lithium salt, and a first additive; the non-aqueous solvent is an ether solvent and a carbonate organic solvent in a mass ratio of 90:10, the ether solvent is DOL+DME in a mass ratio of 1:1, and the carbonate organic solvent is EC and DMC in a mass ratio of 20:80.
[0109] The lithium salt is LiPF6, and the first additive is thiopropirazine (CAS No.: 316-81-4).
[0110] In the electrolyte, the first additive accounts for 1 wt% of the total mass of the electrolyte, and the organic solvent accounts for 85 wt% of the total mass of the electrolyte; the concentration of the lithium salt in the electrolyte is 1 mol / L.
[0111] The method for preparing the electrolyte includes:
[0112] In a glove box with an argon atmosphere containing less than 1 ppm of water and oxygen, ether solvents and carbonate organic solvents are mixed in a predetermined ratio and stirred at room temperature for 30 minutes until completely homogeneous to obtain an organic solvent mixture system.
[0113] The lithium salt was slowly added to the above organic solvent mixture and stirred continuously for 60 minutes until completely dissolved to obtain the basic electrolyte.
[0114] The first additive, thiopropirazine (CAS No.: 316-81-4), was added to the basic electrolyte at a preset ratio and stirred at room temperature for 35 minutes until completely dissolved to obtain the electrolyte.
[0115] Example 2
[0116] This embodiment provides an electrolyte comprising a non-aqueous solvent, a lithium salt, and a first additive; the non-aqueous solvent is an ether solvent and a carbonate organic solvent in a mass ratio of 70:30, wherein the ether solvent is DME, and the carbonate organic solvent is PC and DEC in a mass ratio of 40:60.
[0117] The lithium salt is LiPF6, and the first additive is thiopropirazine (CAS No.: 316-81-4).
[0118] With the total mass of the non-aqueous solvent, the lithium salt, and the first additive being 100 wt%, the first additive accounts for 2 wt% of the total mass of the electrolyte, and the organic solvent accounts for 80 wt% of the total mass of the electrolyte; the concentration of the lithium salt in the electrolyte is 1.5 mol / L.
[0119] The method for preparing the electrolyte includes:
[0120] In a glove box with an argon atmosphere containing less than 1 ppm of water and oxygen, ether solvents and carbonate organic solvents are mixed in a predetermined ratio and stirred at room temperature for 40 minutes until completely homogeneous to obtain an organic solvent mixture system.
[0121] The lithium salt was slowly added to the above organic solvent mixture and stirred continuously for 50 minutes until completely dissolved to obtain the basic electrolyte.
[0122] The first additive, thiopropirazine (CAS No.: 316-81-4), was added to the basic electrolyte at a preset ratio and stirred at room temperature for 40 minutes until completely dissolved to obtain the electrolyte.
[0123] Example 3
[0124] The difference between this embodiment and Embodiment 1 is that in this embodiment, the mass percentage of the first additive is 2 wt% of the total mass of the electrolyte, and the corresponding mass percentage of the non-aqueous solvent is 84 wt%.
[0125] All other conditions remain the same as in Example 1.
[0126] Example 4
[0127] The difference between this embodiment and Embodiment 1 is that in this embodiment, the mass percentage of the first additive is 0.5 wt% of the total mass of the electrolyte, and the corresponding mass percentage of the non-aqueous solvent is 85.5 wt%.
[0128] All other conditions remain the same as in Example 1.
[0129] Example 5
[0130] The difference between this embodiment and Embodiment 1 is that in this embodiment, the mass percentage of the first additive is 0.05 wt% of the total mass of the electrolyte, and the corresponding mass percentage of the non-aqueous solvent is 85.95 wt%.
[0131] All other conditions remain the same as in Example 1.
[0132] Example 6
[0133] The difference between this embodiment and Embodiment 1 is that in this embodiment, the mass percentage of the first additive is 5 wt% of the total mass of the electrolyte, and the corresponding mass percentage of the non-aqueous solvent is 81 wt%.
[0134] All other conditions remain the same as in Example 1.
[0135] Example 7
[0136] The difference between this embodiment and Embodiment 1 is that in this embodiment, the mass percentage of the first additive is 10 wt% of the total mass of the electrolyte, and the corresponding mass percentage of the non-aqueous solvent is 76 wt%.
[0137] All other conditions remain the same as in Example 1.
[0138] Example 8
[0139] The difference between this embodiment and Embodiment 1 is that in this embodiment, n in the first additive is 4, and the structural formula is as follows:
[0140] .
[0141] All other conditions remain the same as in Example 1.
[0142] Example 9
[0143] The difference between this embodiment and Embodiment 1 is that n is 1 in the first additive in this embodiment, and the structural formula is as follows:
[0144] .
[0145] All other conditions remain the same as in Example 1.
[0146] Example 10
[0147] The difference between this embodiment and Example 1 is that the piperazine group and sulfonamide group of the first additive in this embodiment are both unsubstituted groups, and the structural formula is shown below:
[0148] .
[0149] All other conditions remain the same as in Example 1.
[0150] Example 11
[0151] The difference between this embodiment and Embodiment 1 is that the only non-aqueous solvent in this embodiment is carbonate organic solvent.
[0152] All other conditions remain the same as in Example 1.
[0153] Example 12
[0154] The difference between this embodiment and Embodiment 1 is that the carbonate organic solvent in this embodiment contains only the chain carbonate DMC.
[0155] All other conditions remain the same as in Example 1.
[0156] Comparative Example 1
[0157] The difference between this comparative example and Example 1 is that the electrolyte in this comparative example does not contain the first additive, that is, the base electrolyte is the final electrolyte, and the mass ratio of the corresponding non-aqueous solvent is adjusted to 86wt%.
[0158] All other conditions remain the same as in Example 1.
[0159] Comparative Example 2
[0160] The difference between this comparative example and Example 1 is that the first additive in this comparative example is N,N-dimethylphenthiazine-2-sulfonamide (…). CAS No.: 1090-78-4.
[0161] All other conditions remain the same as in Example 1.
[0162] Comparative Example 3
[0163] The difference between this comparative example and Example 1 is that the first additive in this comparative example is 2-chloro-10-[3-(4-methylpiperazin-1-yl)propyl]phenthiazine ( CAS No.: 58-38-8.
[0164] All other conditions remain the same as in Example 1.
[0165] Comparative Example 4
[0166] The difference between this comparative example and Example 1 is that the first additive in this comparative example is N-methylphenthiazide (…). CAS No.: 1207-72-3.
[0167] All other conditions remain the same as in Example 1.
[0168] Comparative Example 5
[0169] The difference between this comparative example and Example 1 is that the first additive in this comparative example is N-dimethyl-1-piperazine sulfonamide (…). CAS No.: 98961-97-8.
[0170] All other conditions remain the same as in Example 1.
[0171] Application Example 1
[0172] This application example provides a lithium-ion battery, which includes a positive electrode, a negative electrode, a separator, and the electrolyte provided in Example 1.
[0173] The method for preparing the lithium-ion battery includes:
[0174] Preparation of positive electrode sheet
[0175] Ternary material NCM (LiNi) 0.8 Co 0.1 Mn 0.1 O2) positive electrode active material, binder PVDF (polyvinylidene fluoride), conductive agent SP (conductive carbon black Super-P) are mixed at a mass ratio of 96:1.8:2.2, and N-methylpyrrolidone (NMP) is added and stirred evenly to obtain a positive electrode slurry with a solid content of 68%. The positive electrode slurry is then coated onto aluminum foil through a coating process, and after drying and cold pressing, a positive electrode sheet is obtained.
[0176] (2) Preparation of negative electrode sheet
[0177] Silicon-carbon anode material (silicon content 12wt%), conductive agent SP (Super-P conductive carbon black), SWCNT (single-walled carbon nanotubes), and binder PAA (polyacrylic acid) were mixed in a mass ratio of 83.5:8:0.5:8, and deionized water was added. The mixture was stirred evenly to obtain an anode slurry with a solid content of 32%. The anode slurry was then coated onto a copper foil current collector through a coating process. After vacuum drying and cold pressing, the anode sheet was obtained.
[0178] (3) Selection of electrolyte
[0179] The electrolyte provided in Example 1.
[0180] (4) Selection of separator membrane
[0181] Polyethylene (PE) + ceramic was chosen as the separator for lithium-ion batteries.
[0182] (5) Preparation of lithium-ion batteries
[0183] The positive electrode, separator, and negative electrode are stacked in sequence, with the separator positioned between the positive and negative electrodes to provide isolation, resulting in a bare cell. The bare cell is then placed in an outer packaging shell, dried, and injected with electrolyte. After vacuum sealing, settling, formation, and shaping, a lithium-ion battery is obtained.
[0184] Application Example 2-12 and Comparison Application Example 1-5
[0185] The difference between Application Examples 2-12 and Comparative Application Examples 1 and Application Example 2-12 is that the electrolytes provided in Examples 2-12 and Comparative Examples 1-5 are used respectively.
[0186] All other conditions remain the same as in Application Example 1.
[0187] Performance testing
[0188] The performance of the lithium-ion battery provided in the above application example was then compared with that of the application example. The test conditions were as follows: the rate performance of the battery was tested under the test conditions of a soft-pack battery, and the test was conducted at room temperature (25°C) on the LADN battery test system of Wuhan Jinno Electronics Co., Ltd. The charge and discharge voltage was limited to 2.5V~4.4V.
[0189] (1) High-temperature storage performance at 60℃
[0190] ① Standard charge and discharge: At 25℃, charge the lithium-ion battery at a constant current and constant voltage rate of 0.33C to 4.2V, let it stand for 10 minutes, then discharge the lithium-ion battery at a constant current rate of 0.33C to 2.5V, and let it stand for 10 minutes.
[0191] ② Initial performance test: The sample battery performance was tested using battery testing equipment at room temperature (25℃). Three standard charge-discharge cycles at 0.33C were performed, and the capacity after the third discharge was recorded. The initial capacity C0 was stored.
[0192] ③ High-temperature storage: At room temperature (25℃), the lithium-ion battery was charged to 4.2V at a constant current and constant voltage rate of 0.33C, left to stand for 30 minutes, and the cell thickness t1 was measured; then the cell was placed in a 60℃ oven for high-temperature storage for 7 days.
[0193] ④ Post-storage performance test: After the storage time is reached, the battery is removed from the high-temperature test chamber and left at room temperature for 2-4 hours to allow the battery temperature to return to room temperature. The cell thickness is measured and recorded as t2. The lithium-ion battery is then discharged at a constant current rate of 0.33C to 2.5V and left to stand for 10 minutes. The discharge capacity is the retention capacity C1. The battery is then subjected to 3 standard charge-discharge cycles at 0.33C, and the capacity of the third discharge is recorded as C2 after storage. The capacity recovery rate after 7 days of storage at 60℃ is calculated as C2 / C0×100%.
[0194] (2) High-temperature cycling performance
[0195] At 45°C, the lithium-ion battery was charged at a constant current and constant voltage of 1C to 4.4V, with a cutoff current of 0.05C. After resting for 10 minutes, the lithium-ion battery was discharged at a constant current of 1C to 2.5V and then rested for 10 minutes. This constitutes one charge-discharge cycle. The lithium-ion battery was subjected to 1000 charge-discharge cycles using the above method. The capacity retention rate of the lithium-ion battery after 1000 charge-discharge cycles at 1C / 1C was calculated.
[0196] The capacity retention rate (%) of a lithium-ion battery after N cycles = (discharge capacity of the Nth cycle / initial discharge capacity) × 100%, where N is the number of cycles of the lithium-ion battery.
[0197] (3) Test of transition metal deposition after high temperature cycling
[0198] After undergoing 1000 high-temperature cycles using the test method in (2), the battery cell was disassembled and the amount of transition metal (Ni+Co+Mn) deposited on the negative electrode was tested by ICP-OES. The calculation basis for the amount of transition metal deposited was the mass of the negative electrode material.
[0199] (4) Cell thermal runaway ARC test
[0200] Begin the ARC adiabatic thermal runaway test (the test sample is heated from room temperature to 45±2℃ inside the chamber, and after resting for 90 minutes, the change in battery temperature rise rate is detected. If the temperature rise exceeds 0.2℃ within 10 minutes (i.e., SHR>0.02℃ / min), it is considered that a self-heating reaction has occurred inside the battery. Maintain the adiabatic environment until the battery experiences thermal runaway; if the temperature rise does not exceed 0.2℃ within 10 minutes (i.e., SHR≤0.02℃ / min), continue to the next step temperature rise test; each temperature step is 5℃, and the steps are repeated on each step. The ARC test temperature range is 45℃~300℃, the self-heating start temperature is T1 (temperature rise rate SHR>0.02℃ / min), and the thermal runaway start temperature is T2 (temperature rise rate SHR>1℃ / min). Note: Self-heating rate (SHR).
[0201] (5) Capacity retention rate at room temperature 1C / 10C discharge
[0202] The lithium-ion battery, after capacity gradation, was charged at 25℃ using a 1C rate with constant current and constant voltage to 4.2V, with a cutoff current of 0.05C; it was then allowed to stand for 10 minutes; next, the lithium-ion battery was discharged at a 1C rate with constant current to 2.5V, and its discharge capacity Q1C was recorded as the initial discharge capacity; then, the lithium-ion battery was charged at 25℃ using a 1C rate with constant current and constant voltage to 4.2V, with a cutoff current of 0.05C; it was allowed to stand for 10 minutes; then, the fully charged battery was discharged at a 10C rate with constant current to 2.5V, and its discharge capacity Q10C was recorded; the discharge capacity retention rate (%) of the lithium-ion battery at 1C / 10C rate was calculated as: discharge capacity Q10C at 10C rate / discharge capacity Q1C at 1C rate × 100%.
[0203] The test results are shown in Table 1.
[0204] Table 1
[0205]
[0206]
[0207] From Table 1, we can obtain:
[0208] The electrolyte provided in this application uses alkyl chains of phenthiazide groups as the parent nucleus and substituted or unsubstituted piperazine groups, as well as organic compounds of substituted or unsubstituted sulfonamide groups as additives. This provides a multi-functional integrated effect of free radical scavenging and flame retardancy, high-voltage anti-oxidation, ordered interfacial film formation, and reversible redox capacity compensation. It breaks through the technical bottlenecks of existing additives, such as single function, compound antagonism, and metal ion side reactions, and improves the high-voltage stability, flame retardant safety, cycle life, and energy density of the battery.
[0209] Data analysis of Examples 1 and 3-7 shows that selecting a suitable mass ratio of 0.05wt% to 5wt% for the first additive can fully leverage its advantages and avoid negative impacts. Further adjusting the mass ratio of the first additive to 0.2wt% to 2wt% is more conducive to the formation of a stable interfacial film at the positive / negative electrode interface and optimizes the redox reversibility and film formation potential of the additive. This avoids the increase in interfacial impedance, electrolyte viscosity, or redox reversibility potential caused by the addition of excessive additives. Thus, while improving high-voltage stability, flame retardant safety, cycle life, and thermal stability, the rate performance of the battery is also taken into account.
[0210] Data analysis of Examples 1 and 8-10 shows that the -(CH2) provided in this application... n In the alkyl chain, further adjusting n to any integer between 3 and 6 is more conducive to balancing the solvent compatibility, electrochemical potential and film-forming activity of the additive; suitable steric hindrance can precisely control the redox potential of the phenothiazine core, achieving synergistic effects of reversible capacity compensation and ordered film formation; at the same time, it avoids the problems of low film-forming potential and easy side reactions between the electrolyte and the positive and negative electrodes during storage caused by n being too small (such as n=1 in Example 9), and also avoids the negative effects of decreased group reactivity, increased electrolyte viscosity and reduced ion transport rate caused by n being too large (such as n≥7); in addition, the substitution of short-chain alkyl groups of piperazine group and sulfonamide group in the first additive further improves the chemical stability of the first additive in high-voltage electrolyte, eliminates the risk of proton side reactions, optimizes molecular steric hindrance and lithium ion coordination ability, and simultaneously improves the cycle life, high-temperature storage stability and rate discharge performance of the battery.
[0211] Data analysis of Examples 1 and 11-12 shows that the first additive provided in this application has better compatibility with the composite solvent of carbonate and ether solvents, and can better exert the multifunctional synergistic effect of the three functional groups of the first additive, phenothiazine, piperazine and sulfonamide, ensuring that the additive is uniformly dispersed and fully dissolved in the electrolyte, avoiding high concentration precipitation, while taking into account both lithium ion conduction efficiency and electrode interface compatibility; in particular, the combination of cyclic carbonate and chain carbonate can take into account the dual advantages of high dielectric constant and low viscosity, which not only promotes the full dissociation of fluorinated lithium salt to improve ionic conductivity, but also has high compatibility with the first additive, synergistically strengthening the stability of the electrode interface film, making the battery's high voltage cycle, rate and thermal safety performance better.
[0212] Analysis of the data from Example 1 and Comparative Examples 1-5 shows that in the electrolyte of this application, the alkyl chain of the phenothiazine group as the core of the substituted or unsubstituted piperazine group and the substituted or unsubstituted sulfonamide group must work together to achieve multifunctional integration. This breaks through the technical bottlenecks of existing additives, such as single function, compound antagonism, and metal ion side reactions, and improves the high voltage stability, flame retardant safety, cycle life and energy density of the battery.
[0213] Example 13
[0214] The difference between this embodiment and Embodiment 1 is that a second additive, FEC, is added to the electrolyte in this embodiment. Based on the total mass of the non-aqueous solvent, the lithium salt, and the first additive being 100wt%, the mass of the second additive added is 5wt%.
[0215] All other conditions remain the same as in Example 1.
[0216] Example 14
[0217] The difference between this embodiment and Embodiment 1 is that a third additive is added to the electrolyte in this embodiment. The third additive is lithium difluorophosphate (LiPO2F2) and triphenyl phosphite (TPPi) in a mass ratio of 1:1. Based on the total mass of the non-aqueous solvent, the lithium salt and the first additive being 100wt%, the added mass of the third additive is 3wt%.
[0218] All other conditions remain the same as in Example 1.
[0219] Example 15
[0220] The difference between this embodiment and embodiment 14 is that the third additive in this embodiment is trimethyl phosphate (TMP).
[0221] All other conditions remain the same as in Example 14.
[0222] Example 16
[0223] The difference between this embodiment and Embodiment 1 is that a fourth additive is added to the electrolyte in this embodiment. The fourth additive is ADN and DTD in a mass ratio of 1:1. Based on the total mass of the non-aqueous solvent, the lithium salt and the first additive being 100wt%, the mass of the fourth additive added is 5wt%.
[0224] All other conditions remain the same as in Example 1.
[0225] Example 17
[0226] The difference between this embodiment and embodiment 16 is that the fourth additive in this embodiment is only ADN.
[0227] All other conditions remain the same as in Example 16.
[0228] Example 18
[0229] The difference between this embodiment and embodiment 16 is that the fourth additive in this embodiment is only DTD.
[0230] All other conditions remain the same as in Example 16.
[0231] Application Example 13-18
[0232] The difference between Application Examples 13-18 and Application Example 1 is that the electrolytes provided in Examples 13-18 are used respectively.
[0233] All other conditions remain the same as in Application Example 1.
[0234] Application Examples 13-18 were tested under the exact same conditions as Application Example 1. The test results are shown in Table 2.
[0235] Table 2
[0236]
[0237] From Table 2, we can obtain:
[0238] Data analysis of Examples 1 and 13-18 shows that, in the electrolyte of this application, in addition to the first additive, a second additive and / or a third additive and / or a fourth additive can be added to further enhance the compounding effect of the additives, and no antagonistic effect will occur due to the compounding of additives.
[0239] Data analysis of Examples 1 and 14-15 shows that when a third additive is added, the combination of lithium difluorophosphate (LiPO2F2) and triphenyl phosphite (TPPi) not only provides dual flame retardancy, but also allows lithium difluorophosphate to participate in interfacial film formation, generating low-resistance phosphorus-containing components, reducing the interfacial impedance of the film formed by the first additive, and guiding the orderly growth of the SEI film by the first additive, providing uniform sites for the decomposition of LiPO2F2 and avoiding impedance unevenness caused by local decomposition.
[0240] Data analysis of Examples 1 and 16-18 shows that the fourth additive, a combination of ADN and DTD, further promotes the antioxidant stability of the electrolyte under high voltage conditions, enhances the density and high-temperature oxidation resistance of the positive electrode CEI film, more effectively inhibits the dissolution of transition metals and the continuous oxidation and decomposition of the electrolyte, and simultaneously improves the battery's high-voltage cycle life, capacity retention rate and thermal safety performance.
[0241] The above description is only a specific embodiment of this application, but the protection scope of this application is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in this application fall within the protection and disclosure scope of this application.
Claims
1. An electrolyte, characterized in that, The electrolyte comprises a non-aqueous solvent, a lithium salt, and a first additive; the first additive has R1-(CH2). n The structural formula described in Ar-R2: Wherein, R1 is selected from substituted or unsubstituted piperazine groups, Ar is a phenothiazine group, R2 is selected from substituted or unsubstituted sulfonamide groups, and n is any integer between 1 and 6.
2. The electrolyte according to claim 1, characterized in that, In the first additive, R1 is selected from an N-substituted piperazine group, and the substituent group in the piperazine group is selected from substituted or unsubstituted straight-chain or branched C1-C4 alkyl groups; And / or, the N-position of the phenothiazine group is linked to -(CH2). n -R1; And / or, the 2-C position of the phenothiazine group is linked to -R2; And / or, in the first additive, R2 is selected from a substituted sulfonamide group, wherein the substituted group in the sulfonamide group is selected from substituted or unsubstituted straight-chain or branched C1-C4 alkyl groups; And / or, in the first additive, n is any integer between 3 and 6.
3. The electrolyte according to claim 1 or 2, characterized in that, The electrolyte has at least one of the following structural formulas (1) to (6): 。 4. The electrolyte according to claim 1 or 2, characterized in that, Based on a total mass of 100 wt% for the non-aqueous solvent, the lithium salt, and the first additive, the mass percentage of the first additive is 0.05 wt% to 5 wt%, preferably 0.2 wt% to 2 wt%. And / or, the non-aqueous solvent includes carbonate organic solvents and / or ether solvents; And / or, based on a total mass of 100 wt% of the non-aqueous solvent, the lithium salt, and the first additive, the mass percentage of the non-aqueous solvent is 80 wt% to 90 wt%; And / or, the lithium salt includes fluorinated lithium salts; And / or, the concentration of the lithium salt is 0.8 mol / L to 1.5 mol / L.
5. The electrolyte according to claim 1, characterized in that, The electrolyte also includes a second additive, which is selected from film-forming additives, including at least one of fluoroethylene carbonate, vinylene carbonate, or 1,3-propanesulfonate lactone. Based on a total mass of 100 wt% for the non-aqueous solvent, the lithium salt, and the first additive, the mass of the second additive added is 0.1 wt% to 8 wt%.
6. The electrolyte according to claim 1, characterized in that, The electrolyte also includes a third additive, which is selected from heat-stabilizing additives, including at least one of lithium difluorophosphate, trimethyl phosphate, or triphenyl phosphite. Based on a total mass of 100 wt% for the non-aqueous solvent, the lithium salt, and the first additive, the mass of the third additive is 0.1 wt% to 5 wt%.
7. The electrolyte according to claim 1, characterized in that, The electrolyte further includes a fourth additive, which is selected from high-voltage antioxidant additives, including at least one of adiponitrile and / or vinyl sulfate. Based on a total mass of 100 wt% for the non-aqueous solvent, the lithium salt, and the first additive, the mass of the fourth additive is 0.1 wt% to 2 wt%.
8. A battery, characterized in that, The battery includes the electrolyte as described in any one of claims 1-7.
9. The battery according to claim 8, characterized in that, The battery operates at a voltage ≥4.4V.
10. An electrical device, characterized in that, The electrical device includes the battery as described in claim 8 or 9.
